Application of Fines for Traffic Violations at Rokan Hilir Police Station - Satria, Dewi; Kusno, Kusno; Ansyari Siregar, Ahmad (International Journal Labs, 2024)
Traffic violations are a persistent issue in road traffic systems globally, including in Indonesia. Despite the enforcement of traffic laws, violations remain prevalent across various regions. This study focuses on the effectiveness of applying criminal fines for traffic violations in the jurisdiction of the Rokan Hilir Police Station and examines the factors that influence these violations. The purpose of this study is to explain the effectiveness of applying criminal fines for traffic violations in the jurisdiction of Rokan Hilir Police Station and explain the factors that influence the occurrence of traffic violations in the jurisdiction of Rokan Hilir Police Station. The results of the first study show that the application of criminal fines for traffic violations at the Rokan Hilir Police Station to date is practical, and this is to the applicable rules by Law Number 22 of 2009 concerning road traffic and transportation. Many traffic violations that occur in the jurisdiction of the Rokan Hilir Police only impose criminal fines, so in the future, imprisonment with the maximum threat must also be applied to traffic violators; this is considering that only the imposition of criminal fines has not provided a deterrent effect on violators. We can see this from the increase in violations that occur every year. The criminal fines imposed have not been able to reduce the level of traffic violations that existed previously in the Rokan Hilir Police jurisdiction, even though they have always been applied to traffic violators in the Rokan Hilir Legal Area. Second, the factors that influence the occurrence of traffic violations in the jurisdiction of the Rokan Hilir Regional Police, among others, are human factors, vehicle factors, and road condition factors.